Ebola and Its Global Research Architecture--Need for an Improvement. - David Quarcoo; Dörthe Brüggmann; Doris Klingelhöfer; David A Groneberg (Public Library of Science (PLoS), 2015)
The current Ebola outbreak poses a threat to individual and global public health. Although the disease has been of interest to the scientific community since 1976, an effective vaccination approach is still lacking. This fact questions past global public health strategies, which have not foreseen the possible impact of this infectious disease. To quantify the global research activity in this field, a scientometric investigation was conducted. We analyzed the research output of countries, individual institutions and their collaborative networks. The resulting research architecture indicated that American and European countries played a leading role regarding output activity, citations and multi- and bilateral cooperations. When related to population numbers, African countries, which usually do not dominate the global research in other medical fields, were among the most prolific nations. We conclude that the field of Ebola research is constantly progressing, and the research landscape is influenced by economical and infrastructural factors as well as historical relations between countries and outbreak events.